CODE SWITCHING AMONG YOUNG GENERATION ON INSTAGRAM - Nanda, Devana (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTThe purpose of this study is to analyze and describe the types and the functions of code switching onInstagram photo captions. The data was taken from Instagram, and was in the form of photo captionsthat fit the criteria of the purposive sampling technique. For the data collection, a qualitative methodwas used. This research applies the theory proposed by Romaine (1995) to classifying the types of codeswitching, and the theory proposed by Appel and Muysken (2005) to describe the function of codeswitching. The results of the study indicate that three types of code switching are found, but of the threetypes of code switching, intra-sentential switching is the most frequently used. The frequent functionsthat occur are referential functions, metalinguistic functions, phatic functions and poetic functions.Keywords: Code switching, The types of Code Switching, The function of Code Switching, InstagramABSTRAKTujuan dari penelitian ini adalah untuk mengetahui jenis alih kode dan fungsi alih kode dalamketerangan foto Instagram. Data diambil dari Instagram, dan berbentuk keterangan foto yangmemenuhi kualitas dari teknik purposive sampling. Untuk pengumpulan data digunakan metodekualitatif. Penelitian ini menerapkan teori yang diusulkan oleh Romaine (1995) untukmengklasifikasikan jenis alih kode, dan teori yang diusulkan oleh Appel dan Muysken (2005) untukmenggambarkan fungsi alih kode. Hasil dari penelitian menunjukkan bahwa tiga jenis alih kode yangditemukan, tetapi dari ketiga jenis alih kode, alih kode intrakalimat yang paling sering digunakan.Fungsi yang sering terjadi adalah fungsi referensial, fungsi metalinguistik, fungsi phatic dan fungsipoetic.Kata kunci: Alih Kode, Jenis Alih Kode, Fungsi Alih Kode, Instagram